2018
DOI: 10.1037/dhe0000056
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived educational environment and high school generation on Mexican American female community college students’ emic well-being.

Abstract: Using a psychosociocultural approach, the study examined the mediating role of the perceptions of the community college environment and moderating influence of being first to graduate high school, on the relationships between coping and self-esteem with emic well-being, respectively. A total of 160 Mexican American female students were included in the study. Perceptions of the environment mediated the relationship between coping and emic well-being and partially mediated the relationship of selfesteem and emic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Within the PSC theoretical framework, how comfortable one feels on campus was found to predict Latina/o college student academic persistence decisions (Delgado-Guerrero & Gloria, 2013) and was mediated only by an Anglo ethnic orientation, but not a Mexican ethnic orientation (Aguinaga & Gloria, 2015). Similarly, Herrera et al (2018) found that Mexican-American women students who were the first in their family to graduate from high school felt less comfortable on a community college campus. Castellanos and Gloria (2007) recommended that various types of cultural programming be implemented on campus to create an environment that is culturally inviting.…”
Section: Cultural Dimension: Cultural Programming On Campusmentioning
confidence: 95%
See 2 more Smart Citations
“…Within the PSC theoretical framework, how comfortable one feels on campus was found to predict Latina/o college student academic persistence decisions (Delgado-Guerrero & Gloria, 2013) and was mediated only by an Anglo ethnic orientation, but not a Mexican ethnic orientation (Aguinaga & Gloria, 2015). Similarly, Herrera et al (2018) found that Mexican-American women students who were the first in their family to graduate from high school felt less comfortable on a community college campus. Castellanos and Gloria (2007) recommended that various types of cultural programming be implemented on campus to create an environment that is culturally inviting.…”
Section: Cultural Dimension: Cultural Programming On Campusmentioning
confidence: 95%
“…The PSC framework has been used to examine various college outcomes for groups of Latina/o students, such as academic persistence decisions (Aguinaga & Gloria, 2015), sense of mattering on campus (Dueñas & Gloria, 2017), GPA (Chun et al, 2016), Latina sorority members’ academic persistence decisions (Delgado-Guerrero & Gloria, 2013), and Mexican-American women community college students’ emic well-being (Herrera et al, 2018). In general, prior studies have demonstrated that various psychological (e.g., self-esteem; Herrera et al, 2018), social (e.g., perceived social support; Delgado-Guerrero and Gloria, 2013), and cultural factors (e.g., match between students’ culture and the institution’s culture; Dueñas and Gloria, 2017) are related to the aforementioned college outcomes. Several studies have also demonstrated that the university environment (e.g., feeling valued or comfortable on campus) plays a crucial role in the psychological well-being of Latina/o students on campus (Aguinaga & Gloria, 2015; Delgado-Guerrero & Gloria, 2013; Herrera et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A mediation model dimension-specific focus addresses unique nuances of educational outcomes focusing on how the constructs “work” discretely to inform the PSC approach holistically (e.g., Aguinaga & Gloria, 2015; Dueñas & Gloria, 2017). For example, previous studies took an individual dimension-focused, mediation model approach via focus on the “Cultural” dimension (Aguinaga & Gloria, 2015; Castillo et al, 2006; Herrera et al, 2017). The present study similarly the same approach culture dimension-focused aproach by examining whether cultural congruity would further explain the relationships among self-efficacy (psychological), perceived social support from family (social), and ethnic identity (cultural) to coping, respectively.…”
Section: Guiding Theoretical Frameworkmentioning
confidence: 99%